Implementation of the Independent Curriculum Using the CIPPO Model at Vocational High Schools in Makassar - Mangesa, Riana; Makmur, Elfira; Nurfardhilah, Nurfardhilah (Letters in Information Technology Education (LITE), 2024)
This study is evaluation research using the CIPPO model, which aims to evaluate the implementation of the Merdeka Curriculum in vocational high schools (SMK) in Makassar, considering four aspects: context, input, process, product, and outcome. The subjects of this study consist of school supervisors, principals, vice principals in charge of curriculum, teachers, and students selected using purposive sampling techniques. Data collection techniques include interviews, questionnaires, and documentation. The data was obtained by distributing questionnaires online through Google Forms. The data analysis technique used is descriptive analysis. The study results indicate that: (1) Context evaluation covering two indicators achieved a percentage of 97 percent, with a criterion of excellent. (2) Input evaluation covering four indicators achieved a percentage of 89 percent, with a criterion of excellent. (3) Process evaluation covering three indicators achieved a percentage of 93 percent, with a criterion of excellent. (4) Product evaluation covering three indicators achieved a percentage of 97 percent, with a criterion of excellent. (5) Outcome evaluation covering three indicators achieved a percentage of 92 percent, with a criterion of excellent. Based on the results of the study, it can be concluded that the evaluation of the implementation of the Merdeka Curriculum in vocational high schools in Makassar is considered excellent.